The Effect of Gender-Targeted Conditional Cash Transfers on Household Expenditures: Evidence from a Randomized Experiment - Alex Armand; Orazio Attanasio; Pedro Carneiro; Valerie Lechene (Institute for the Study of Labor (IZA), 2016)
This paper studies the differential effect of targeting cash transfers to men or women on the structure of household expenditures on non-durables. We study a policy intervention in the Republic of Macedonia, offering cash transfers to poor households, conditional on having their children attending secondary school. The recipient of the transfer is randomized across municipalities to be either the household head or the mother. Using data collected to evaluate the conditional cash transfer program, we show that the gender of the recipient has an effect on the structure of expenditure shares. Targeting transfers to women increases the expenditure share on food by about 4 to 5%. To study the allocation of expenditures within the food basket, we estimate a demand system for food and we find that targeting payments to mothers induces, for different food categories, not only a significant intercept shift, but also a change in the slope of the Engel curve.
Keywords: D12; D13; E21; O12; 330; CCT; intra-household; gender; expenditure